COVID-19 Lockdown and Creativity: Exploring the Role of Emotions and Motivation on Creative Activities From the Chinese and German Perspectives - Hofreiter, Sebastian; Zhou, Xiang; Tang, Min; Werner, Christian H.; Kaufman, James C. (Frontiers in Psychology, 2021)
For much of 2020, countries around the world fought against the COVID-19 pandemic. Many countries went into lockdown to control the fast spread of the virus. The unusual restrictions and confinement of the lockdown brought about new challenges for people’s everyday lives. With flexibility, adaptability, and problem-solving at the core of its nature, creativity has the potential to help people cope with harsh and uncertain circumstances. Were people more, the same, or less creative in their everyday life during the period of lockdown, and in which ways? What are the emotions and motivations underlying their creative or non-creative behaviors? The current study aims to explore these questions from a cross-cultural perspective. A total of 754 comparable employee samples from three Chinese and three German cities were asked about their moods during the lockdown period, their self-rated level of creativity in daily lives before and during the lockdown, and their motivations behind their creative activities. Significant increases in creativity were observed in all everyday activities in both countries with only two exceptions in the German sample. Despite minor differences, a common pattern was found across cultures: whereas the activating positive mood could directly lead to the increase in creativity in some everyday activities, such a direct Mood-Creativity link was limited in the activating negative mood circumstances. In such circumstances, motivation intervened to enable the link to creativity. It was also found that this indirect effect of motivation between mood and creativity was more pronounced with the German participants.